A study on metaphor in terminology for finance and banking in English and Vietnamese = Nghiên cứu các ẩn dụ trong thuật ngữ kinh tế ngành Tài chính- Ngân hàng trong Tiếng Anh Và Tiếng Việt - Vũ, Thị Thùy Linh (2021)
It is undeniable that there are numerous reasons for the growing popularity of metaphors in business and economics, not only in linguistic world. However, the previous researches is just conducted to have a general view about metaphor using in economics so there has been little research on metaphorical terms themselves as a target of the study. As an attempt to contribute to gaining more insights into metaphorical term in finance and banking, this research aims to reveal much inside metaphor in economics, from that, some suggestions would also be given. Finally, it can be made step-by-step about the application and exploitation of other rhetorical measures in economics terms in other branches of economics study. These goals were achieved by a research using document observation and using both qualitative and quantitative analysis. Findings from the study show that similarities and difficulties of basic transferences and source domains among English and Vietnamese metaphorical terms in finance and banking. The study also suggests some aspects of metaphor for students to invest for their further study. Hopefully, students and researchers can use it as a helpful material for their graduation thesis as well as their post-graduation thesis.